CONCORDANCE OF TENSES IN FRENCH - Radjabov Ruslan Radjabmurodovich; Djumaboeva Marjona Farhod kizi (Western European Studies, 2025)
Concordance of tenses (ou concordance des temps) is an important aspect of French grammar. It determines how tenses in the main and subordinate clauses relate to each other. Mastering the rules of conjugation of tenses not only enriches written and spoken language, but also allows you to better understand the nuances of the French language
Keywords: Verbs; Subordinate Clause; Subjunctive Mood